Effect of Citric Acid and Ethylenediaminetetraacetic Acid on the Surface Morphology of Young and Old Root Dentin - Zaccaro Scelza, Miriam; de Noronha, Fernando; da Silva, Licinio Esmeraldo; MaurÃcio, Marcos; Gallito, Marco Antonio; Scelza, Pantaleo (Iranian Endodontic Journal, 2016)
Introduction: The aim of this in vitro study was to evaluate the effect of 10% citric acid and 17% ethylenediaminetetraacetic acid (EDTA) irrigating solutions on the surface morphology of young and old root dentin by determining the number and diameter of dentinal tubules using scanning electron microscopy (SEM). Methods and Materials: Fifty healthy human teeth collected from young (≤30 years) and old (≥60 years) individuals (n=25) were first prepared with a Largo bur #2 to produce smear layer on the root canal surface. Subsequently, the crowns and the root middle and apical thirds were sectioned and removed, and the cervical thirds were sectioned vertically in the buccal-lingual direction into two equal halves. The obtained samples were then immersed in 2.5% sodium hypochlorite for 30 min and randomly separated into two treatment groups for each age group. In each age group, ten samples were selected as controls and did not receive any type of treatment. The rest of the specimens were then rinsed, dried and treated for 4 min with 10% citric acid or 17% EDTA. The samples were then assessed with SEM regarding the number and diameter of dentinal tubules. All data were assessed using Student’s t-test. The level of significance was set at 0.05. Results: Regardless of the type of treatment, no significant differences were observed in the number of open tubules between the young and old root dentin (P>0.05). Nonetheless, the diameter of the tubules in the old root dentin was larger when 17% EDTA was used (P<0.05). Both, young and old root dentin did not differ with the 10% citric acid treatment (P>0.05). Conclusion: The results showed that 17% EDTA treatment induced a significant demineralization in old root dentin. Keywords: Citric Acid; Dentinal Tubule; Ethylenediaminetetraacetic Acid; Scanning Electron Microscopy; Surface Morphology